Treatment goals for rheumatoid arthritis: patient engagement and goal collection - Zachary Predmore; Emily K Chen; Thomas W Concannon; Suzanne Schrandt; Susan J Bartlett; Clifton O Bingham; Richard Z Xie; Richard H Chapman; Lori Frank (Becaris Publishing Limited, 2023)
Aim: We developed the Patient-Engaged Health Technology Assessment strategy for survey-based goal collection from patients to yield patient-important outcomes suitable for use in multi-criteria decision analysis. Methods: Rheumatoid arthritis patients were recruited from online patient networks for proofof- concept testing of goal collection and prioritization using a survey. A Project Steering Committee and Expert Panel rated the feasibility of scaling to larger samples. Results: Survey respondents (n = 47) completed the goal collection exercise. Finding effective treatments was rated by respondents as the most important goal, and reducing stiffness was rated as the least important. Feedback from our steering committee and expert panel support the approach's feasibility for goal identification and ranking. Conclusion: Goals relevant for treatment evaluation can be identified and rated for importance by patients to permit wide input from patients with lived experience of disease.